2011
DOI: 10.1177/1028315311403936
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Intercultural Contact on Campus

Abstract: International students' adjustment to living in an unfamiliar cultural environment and studying in a different educational system and language has been a topic of much research. Literature has shown that support from the host community could be the difference between a smooth transition and one fraught with problems and difficulties. This article describes a "buddy project" used in an intercultural communication class in which each student was a buddy for a newly arrived international student for a semester. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…It was found that international students face barriers in developing and sustaining social networks in the host community, and poor social integration was even identified as a potential factor impeding the academic progress of international students. Our findings concur with the findings of a substantial amount of literature published on the issues on integration of international students, including researches done by Stronkhorst (2005)and Campbell (2012). Findings here show that even within joint degree studies (which have deeper and closer interaction between HEIs than many other activities of international cooperation) international students' isolation from the local students of hosting partner institutions remains very relevant.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It was found that international students face barriers in developing and sustaining social networks in the host community, and poor social integration was even identified as a potential factor impeding the academic progress of international students. Our findings concur with the findings of a substantial amount of literature published on the issues on integration of international students, including researches done by Stronkhorst (2005)and Campbell (2012). Findings here show that even within joint degree studies (which have deeper and closer interaction between HEIs than many other activities of international cooperation) international students' isolation from the local students of hosting partner institutions remains very relevant.…”
Section: Discussionsupporting
confidence: 91%
“…Despite the scarcity of research on the quality of the teaching and learningprocess injoint degree studies, a considerable amount of literature has been published on the development of students' intercultural competence and development of their competencies in professional situations within the international environment. Findings of some studies (Campbell, 2012;Sample, 2012) indicate that a crucial step on the path to developing intercultural competence is curriculum and appropriate interventions (special training, assignments, etc.). Findings of studies dedicated to the employability of international students (Cai, 2012;Barker & Mak, 2013) show that despite the importance of cross-cultural skills, such skills per se will not guarantee employment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Institutionalized peer tutoring is one way that universities facilitate contact between international students and host nationals [80] and help make the transition process more positive [81]. To optimize the success of tutor programs, Campbell [81] recommends a combination of large group, small group, and one-on-one activities.…”
Section: Implications For International Education Policymentioning
confidence: 99%
“…Theu niversity should implements ofts kills development instructional programmes both in and out of classroom activities to enhance students' interculturalc ompetencies in which intercultural sensitivity is one of the core domains of intercultural competencies. Programme such as cross-ethnic pairing in campus dormitories (Espenshade &Radford, 2009), cross-ethnic buddy project (Campbell, 2012) and ethnic-related service learning have found to impact positively on students' cultural competencies (Astin, Vogelgesang,Ikeda,&Yee, 2000) and civic-engagement (Bowman, 2011). If the universities want to improveorstrengthen interethnic bridgingsocial capital among the students, they mustdeliberately provide the students greater access to ethnicrelated diversity experiences by increasing opportunities for greater interethnic contact and interaction beyond classroom settings.…”
Section: Discussionmentioning
confidence: 99%